Effect of progesterone sequential therapy on follicle stimulating hormone (FSH), luteinizing hormone (LH), and estradiol (E2) in perimenopausal dysfunctional uterine bleeding - Wu Song; Wang Huiru; Zhao Yuwei; Tang Bo; Zhang Qi; Li Dapeng (Journal of Medical Biochemistry)
Background: Perimenopausal dysfunctional uterine bleeding (PDUB) is a common gynaecological disease with various clinical treatment options. The objective of this work was to investigate the clinical effect of female progesterone sequential therapy (FPST) on PDUB and follicle-stimulating hormone (FSH), luteinizing hormone (LH), and estradiol (E2). Methods: 140 cases of PDUB patients were enrolled and randomly rolled into an observation (Obs) group and a control (Ctrl) group, with 70 cases in each. The patients in the Ctrl group were given pure curettage treatment, and those in the Obs group were supplemented with FPST based on the intervention in the Ctrl group. Results: The therapeutic effects of patients in different groups were compared. The cure rate (CR) and total effective rate (TER) in the Obs group were 84.26% and 97.14%, respectively, which were much higher than those in the Ctrl group (44.29% and 74.29%), showing great differences (P< 0.05). The incidence of adverse reactions in the Obs group and Ctrl group were 4.29% (3/70) and 2.86% (2/70), respectively, exhibiting no great difference (P> 0.05). Additionally, after 3 months of follow-up, the recurrence rate was 1.43% (1/70) in the Obs group, which was much higher than 44.29% (31/70) in the Ctrl group, presenting a remarkable difference with P< 0.05. Auda Furqan Moein.